Critical Factors for Women’s Representation in Top Management Leadership Positions in Local Government - Frans Budiman Johannes; Aloysius Liliweri; Frans Gana; Nursalam Nursalam (Magister Administrasi Publik, 2022)
This study explores the critical factors behind women’s representation in upper-echelon II managerial positions in local government organizations in Indonesia, which contemporary studies rarely studied. This research interviewed 12 informants at the East Nusa Tenggara (ENT) Provincial Government in Indonesia using a qualitative approach and purposive sampling techniques. This article found eight factors that are critical in influencing women's representation in echelon II positions in local government organizations from three primary dimensions. First, a network of political proxies and representation of ethnicity and electoral areas are factors from the socio-political dimension. Second, the three factors related to the intra-organizational dimension are patriarchal culture, gender stereotypes, and masculine leadership. Lastly, academic respect, self-confidence, and domestic responsibility are three factors from the individual dimension. The practical implication of this study is that for women to be elected to echelon II positions, they need to expand their network or political connections with political party leaders affiliated with elected political officials or the family actors of elected political officials. Additionally, women must adopt masculine leadership models to be accepted by their male colleagues and adapt to a patriarchal organizational environment. Finally, women need to increase their confidence in a leadership capacity.